The double-edged sword of statins in intracerebral hemorrhage patients: a systematic review and meta-analysis - Zheng Li; Wen-qi Xu; Jiao-qi Wang; Jia-hui Yang; Xiao-hua Shi; Cheng-bing Wang; Zhong-xin Xu; Jin-lan Jiang (Frontiers in Neurology)
BackgroundThis meta-analysis aimed to investigate the effect of statins on the prognosis of patients with intracerebral hemorrhage (ICH).MethodsWe conducted a systematic search using the keywords “statin” and “intracerebral hemorrhage” across four electronic databases (PubMed, Cochrane Library, Web of Science, and Embase) from their inception to October 31, 2023, to identify studies comparing the effects of statins on the prognosis of patients with ICH. The primary outcome was total mortality after ICH. This meta-analysis was registered online (PROSPERO ID: CRD42023493063).ResultsOur initial search identified 5,543 studies. After applying inclusion criteria, 30 studies with a total of 42,298 patients were included in the final analysis. Our meta-analysis showed that statins significantly reduced overall mortality in patients with ICH (OR: 0.61; 95% CI: 0.51–0.73; I2 = 87%; p < 0.01). Subgroup analyses further demonstrated lower mortality in ICH patients treated with statins compared to those not treated, including in the propensity score matching (PSM) group (OR: 0.59; 95% CI: 0.48–0.74; I2 = 90%; p < 0.01), the prospective cohort study (PCS) group (OR: 0.56; 95% CI: 0.40–0.77; I2 = 89%, p < 0.01), and the retrospective cohort study (RCS) group (OR: 0.64; 95% CI: 0.51–0.81; I2 = 87%, p < 0.01).ConclusionOur meta-analysis of 30 studies suggests that statin use may be associated with improved mortality and functional outcomes in patients with intracerebral hemorrhage (ICH).Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, CRD42023493063.